A tool for detection of the connection between domestic violence and companion animal mistreatment in Botucatu, São Paulo, Brazil - Tremori, Tália Missen [UNESP]; Everson, Mariel Adan [UNESP]; Santeramo, Juliana; Gomes, Laiza Bonela; Reis, Sérvio Túlio Jacinto [UNESP]; Ribas, Laila Massad [UNESP]; Massad, Mara Rita Rodrigues [UNESP]; Rocha, Noeme Sousa [UNESP] (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2024)
There is a well-established link intersecting animal cruelty and interpersonal violence that suggests domestic violence can be an indicator of pet mistreatment and other forms of aggression. In Brazil, despite the high rate of domestic violence, there has been little research on the link between domestic violence and animal cruelty. This study aims to propose a tool for detecting animal cruelty in homes where domestic violence against women occurs and for clinical evaluation of animal victims. For the study, 145 Incident Reports (BO) from the Defense of Women Police Station (DDM) of Botucatu, SP, Brazil, were analyzed, and 55 women responded to a voluntary questionnaire about violence against animals. Thirty-one women claimed to own animals at their residence, totaling 54 dogs and 26 cats. Among those women who had animals and answered the questionnaire, it was verified that 14 women (45%) revealed physical violence towards animals by the same aggressor. The clinical examination of animals confirmed that 11 animals had a poor body score index and were in a mistreatment situation. The questionnaire provided valuable information and represented a potential tool that can be used by veterinarians, security, and social professionals to assess cases of domestic violence and comprehension of the welfare of pet animals.
Ferramenta para detecção da conexão de violência doméstica e maus-tratos a animais de companhia em Botucatu, São Paulo, Brasil
Keywords: Animal abuse; Animal behavior; Animal cruelty; Link theory